Placental thickness and its correlation to gestational age estimated by fetal biometry: A cross-sectional study - Ashwini Nagesh Naik; Sushilkumar Kale; Atul Tayade; Dhananjay Ghodke (Asian Journal of Medical Sciences, 2022)
Background: Accurate estimation of gestational age is important not only for appropriate antenatal care but also is crucial for undertaking various diagnostics tests such as chorionic villous sampling and amniocentesis. In certain conditions, where biometry cannot be entirely relied on for estimation of gestational age placental thickness (PT) that can be used for estimation of gestational age. Aims and Objectives: The aims of this study were as follows: (1) To analyze relationship between PT and gestational age as determined by fetal biometry in second and third trimester of pregnancy. (2) To find out cutoff PT value for differentiating between preterm and term gestations. Materials and Methods: This was a cross-sectional, in which 140 patients, in 2nd and 3rd trimester, were included on the basis of a predefined inclusion and exclusion criteria. PT was measured in mm along with their respective standard deviation. The correlation between PT and gestational age as determined by biometry. Results: The mean age of the studied cases was found to be 4.15±3.5 years. At 12 weeks of gestation, the mean PT was 14.36 mm. There was a strong positive correlation between gestational age and PT in 2nd (r=0.9943) and 3rd (r=0.9973) trimesters. After 37 weeks of gestation, there was no significant correlation between PT and gestational age (P=0.469). Conclusion: PT has a significant positive correlation with gestational age in 2nd and 3rd trimester of pregnancy (up to 37 weeks of gestation) and can be reliably used for determination of gestational age independent of fetal biometry.